A silver Nanoparticle/Poly (8-Anilino-1-Naphthalene Sulphonic Acid) Bioelectrochemical Biosensor System for the Analytical Determination of Ethambutol - Ngece, Rachel F; West, Natasha; Ndangili, Peter M; Olowu, Rasaq A; Williams, Avril; Hendricks, Nicolette; Mailu, Stephen N.; Baker, Priscilla; Emmanuel, Iwuoha (My University, 2011)
Ethambutol (2S, 2′S)-2, 2′-(ethane-1, 2-diyldiimino) dibutan-1-ol) is a first-line antitubercular drug effective against actively growing Mycobacterium tuberculosis. Resistance of the mycobacterium to ethambutol among tuberculosis (TB) patients results from inadequate or inappropriate dosing of treatment or using low quality medication. It is therefore necessary to develop reliable methods for determining the ethambutol metabolic profile of patients at point of care for proper dosing. Herein an efficient ethambutol bioelectrochemical nanosensor device is illustrated. It consists of cytochrome P450-2E1 (CYP2E1) immobilised on electroactive nanocomposites of poly (8-anilino-1-napthalene sulphonic acid) (PANSA) and silver nanoparticles (AgNPs) stabilized in polyvinylpyrrolidone (PVP). The performance of the ethambutol nanobiosensor (Au/ PANSA/AgNPs /CYP2E1) was interrogated amperometrically. The biosensor gave a dynamic linear range of 2-12 µM, a sensitivity of 1.125µA/µM, detection limit of 0.7 µM and an apparent Michaelis-Menten constant (KMapp) of 1,008 µM. The low detection limit and the dynamic linear range make the nanobiosensor very suitable for the determination of ethambutol in serum.
Keywords: Ethambutol; Cytochrome P450-2E1 (CYP2E1); Silver nanoparticles; Poly (8-anilino-1napthalene sulphonic acid) (PANSA); Tuberculosis (TB)